2015
DOI: 10.1007/s12035-015-9264-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TDP-43 in Alzheimer’s Disease

Abstract: The transactive response DNA binding protein (TDP-43) has long been characterized as a main hallmark of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitin-positive inclusions (FTLD-U, also known as FTLD-TDP). Several studies have indicated TDP-43 deposits in Alzheimer's disease (AD) brains and have robust connection with AD clinical phenotype. FTLD-U, which was symptomatically connected with AD, may be predictable for the comprehension of the role TDP-43 in AD. TDP-43 may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 92 publications
3
43
0
Order By: Relevance
“…6 and Table 2). Our results are in accordance with previous reports which indicate that, in advanced AD cases, TDP43 positive cytoplasmic inclusions are found in around 75% of the cases [38]. Finally, we have measured the number of A␤ plaques in CA1 region for each case which, as expected, correlates with the severity of the disease (see Supplementary Fig.…”
Section: At100/ps396 Ratio and Braak Stagesupporting
confidence: 92%
“…6 and Table 2). Our results are in accordance with previous reports which indicate that, in advanced AD cases, TDP43 positive cytoplasmic inclusions are found in around 75% of the cases [38]. Finally, we have measured the number of A␤ plaques in CA1 region for each case which, as expected, correlates with the severity of the disease (see Supplementary Fig.…”
Section: At100/ps396 Ratio and Braak Stagesupporting
confidence: 92%
“…Conversely, approximately 40% of DLB patients have AD pathology as determined by their CSF-biomarker profile [199]. Furthermore, up to half of AD patients harbour transactive response DNA-binding protein 43 (TDP-43) inclusions that are characteristic of frontotemporal lobar degeneration (FTLD) and sporadic amyotrophic lateral sclerosis (ALS) [7, 50, 159]. Amylin deposits, which are found in the pancreas of most patients with type 2 diabetes mellitus, have also been found in AD (and type 2 diabetes) brains [157].…”
Section: Alzheimer’s Disease Pathological Mechanismsmentioning
confidence: 99%
“…Under pathophysiological conditions, TDP-43 accumulates in the cytoplasm and is hyperphosphorylated and/or ubiquitinated, and this is characteristic of the cytoplasmic inclusions observed in ALS and in many cases of FTLD [51, 265]. TDP-43 pathology is also detected in 20–50% of AD patients [7, 50, 159], and appears to be associated with greater brain atrophy, memory loss, and cognitive impairment [50, 163]. Studies suggest that TDP-43 pathology can be triggered by Aβ peptides, and that TDP-43 contributes to neuroinflammation and may have a role in mitochondrial and neural dysfunction [50].…”
Section: Tdp-43 Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Since TDP-43based neuropathology is present in ~50% of FTLD and ~97% of ALS cases (16), TDP-43 represents a molecular link connecting these neurodegenerative diseases as a clinicopathological spectrum of the proteinopathies (14,(17)(18)(19) . It was also pointed out that TDP-43 may contribute to the pathogenesis of Alzheimer's disease (AD) via both β-amyloid (Aβ)dependent and Aβ-independent pathways (20). Furthermore, TDP-43 abnormalities have also been associated with traumatic brain injury (chronic traumatic encephalopathy) in both pre-clinical and clinical studies (7) and observed in cognitively impaired persons in advanced age with hippocampal sclerosis, Huntington's disease and some other maladies (21).…”
Section: Introductionmentioning
confidence: 99%